The Redox Biology of Excitotoxic Processes: The NMDA Receptor, TOPA Quinone, and the Oxidative Liberation of Intracellular Zinc - Aizenman, Elias; Loring, Ralph H.; Reynolds, Ian J.; Rosenberg, Paul A. (Frontiers in Neuroscience, 2020)
This special issue of Frontiers in Neuroscience-Neurodegeneration celebrates the 50th anniversary of John Olney’s seminal work introducing the concept of excitotoxicity as a mechanism for neuronal cell death. Since that time, fundamental research on the pathophysiological activation of glutamate receptors has played a central role in our understanding of excitotoxic cellular signaling pathways, leading to the discovery of many potential therapeutic targets in the treatment of acute or chronic/progressive neurodegenerative disorders. Importantly, excitotoxic signaling processes have been found repeatedly to be closely intertwined with oxidative cellular cascades. With this in mind, this review looks back at long-standing collaborative efforts by the authors linking cellular redox status and glutamate neurotoxicity, focusing first on the discovery of the redox modulatory site of the N-methyl-D-aspartate (NMDA) receptor, followed by the study of the oxidative conversion of 3,4-dihydroxyphenylalanine (DOPA) to the non-NMDA receptor agonist and neurotoxin 2,4,5-trihydroxyphenylalanine (TOPA) quinone. Finally, we summarize our work linking oxidative injury to the liberation of zinc from intracellular metal binding proteins, leading to the uncovering of a signaling mechanism connecting excitotoxicity with zinc-activated cell death-signaling cascades.